Problems Existing in Urban Air Pollution Control and Their Optimization Measures - Li Tianxuan (MATEC Web of Conferences)
Urban air pollution has become one of the prominent environmental problems facing the world. Although the implementation of the Chinese government’s Air Pollution Prevention and Control Action Plan and other policies has improved the air quality indicators, there are still major problems, such as a single energy structure, insufficient dust supervision, and excessive pollutant emissions in local areas, and the measures need to be further optimized. This paper focuses on controlling urban air pollution and adopts the comprehensive analysis method. The research deeply discusses the main problems in urban air pollution control and puts forward optimization strategies. It is suggested that clean energy be turned to, dust control measures strengthened, and coordinated emission reduction of multiple pollutants promoted. The results show that while China has made some progress in improving air quality, addressing these challenges is crucial to continuously improving air quality. Therefore, it is urgent to optimize the energy structure, strengthen the dust control measures, and promote the coordinated emission reduction of multiple pollutants, which needs to be highly valued and effectively implemented to ensure human health and ecosystem safety.